2001
DOI: 10.1007/bf03016698
|View full text |Cite
|
Sign up to set email alerts
|

Les pressions élevées du masque laryngé, causées par le protoxyde d’azote, n’augmentent pas les lésions muqueuses chez les chiens

Abstract: P Pu ur rp po os se e: : During general anesthesia, nitrous oxide (N 2 O) diffuses rapidly into the air-filled laryngeal mask airway (LMA) cuff, increasing intracuff pressure. There is no clear correlation between LMA intracuff pressure and pressure on the pharynx. We have studied the effects of high LMA intracuff pressures secondary to N 2 O on the pharyngeal mucosa of dogs.M Me et th ho od ds s: : Sixteen mongrel dogs were randomly allocated to two groups: G1 (intracuff volume, 30 mL; n=8) breathed a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[20,18] Study with the PLMA suggested that directly measured mucosal perfusion pressure rarely exceeded 25 mmHg [7] and therefore, did not increase pharyngeal mucosal injury, while others recommend reducing the cuff volume until it just seals the leak . [21,22] The cuffs of PLMA inflated with maximum recommended cuff volumes, exerted lower pressures predominantly below 15 mmHg on the pharyngeal and hypopharyngeal mucosa. It was also reported that PLMA along with nasogastric tube, induce significantly higher pharyngeal pressures in posterior location when compared to other devices.…”
Section: Discussionmentioning
confidence: 99%
“…[20,18] Study with the PLMA suggested that directly measured mucosal perfusion pressure rarely exceeded 25 mmHg [7] and therefore, did not increase pharyngeal mucosal injury, while others recommend reducing the cuff volume until it just seals the leak . [21,22] The cuffs of PLMA inflated with maximum recommended cuff volumes, exerted lower pressures predominantly below 15 mmHg on the pharyngeal and hypopharyngeal mucosa. It was also reported that PLMA along with nasogastric tube, induce significantly higher pharyngeal pressures in posterior location when compared to other devices.…”
Section: Discussionmentioning
confidence: 99%
“…[22] However, another study with the PLMA suggested that directly measured mucosal perfusion pressure rarely exceeded 25 mmHg[19] and therefore, did not increase pharyngeal mucosal injury, while others recommend reducing the cuff volume until it just seals the leak. [2324]…”
Section: Discussionmentioning
confidence: 99%
“…Ciliated pseudostratified respiratory epithelium and the stratified squamous epithelium which cover the laryngo-pharyngeal mucosa are relatively resistant to minor injury. 13 Williams et al 14 suggested that at constant suboptimal humidity, an increasing exposure time increases mucosal dysfunction. Asmundsson et al 15 also suggested that irreversible cessation of ciliary activity leading to inflammation and sloughing of the upper airway mucosa requires an exposure time to dry gases of more than three hours.…”
Section: Discussionmentioning
confidence: 99%